2023
DOI: 10.1021/acs.iecr.3c02599
|View full text |Cite
|
Sign up to set email alerts
|

Base-Free Oxidative Esterification of HMF Using Mg–Al Hydrotalcite-Supported Gold Catalyst

Xusheng Guo,
Yuxi Si,
Yuanchao Huang
et al.

Abstract: Gold-catalyzed oxidative esterification of 5-hydroxymethylfurfural (HMF) under basic conditions is a promising process to produce dimethyl-2,5-furan dicarboxylate (DMFD). However, it has been overlooked that the DMFD readily hydrolyzes in the presence of soluble bases. Herein, we report solid basesupported gold catalysts for the base-free conversion of HMF. The catalysts' basic sites (BSs) were found to facilitate the esterification of aldehydes and oxidation of alcohols to aldehydes. Moreover, the properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…While there was no difference in MFFC conversion, the MFDC yield without Na 2 CO 3 was higher than those with Na 2 CO 3 (4-10 mol %). The lower MFDC yields are due to base-assisted several side reactions such as the stepwise hydrolysis of MFDC to FDCA [24,40] and the base-catalyzed Cannizaro reaction of MFFC to MHMFC, the latter of which forms the humin-type byproducts via polymerization with the unreacted substrate. [13,23] The base-free oxidative esterification of MFFC with Au/CeO 2 afforded MFDC in an excellent yield of 93 %.…”
Section: Oxidative Esterification Of Mffc To Mfdc (10 Wt %) With Au/ceomentioning
confidence: 99%
“…While there was no difference in MFFC conversion, the MFDC yield without Na 2 CO 3 was higher than those with Na 2 CO 3 (4-10 mol %). The lower MFDC yields are due to base-assisted several side reactions such as the stepwise hydrolysis of MFDC to FDCA [24,40] and the base-catalyzed Cannizaro reaction of MFFC to MHMFC, the latter of which forms the humin-type byproducts via polymerization with the unreacted substrate. [13,23] The base-free oxidative esterification of MFFC with Au/CeO 2 afforded MFDC in an excellent yield of 93 %.…”
Section: Oxidative Esterification Of Mffc To Mfdc (10 Wt %) With Au/ceomentioning
confidence: 99%
“…This catalytic activity stems from the generation of Lewis acidic site by introducing Mo as proved by pyridine FTIR [133] . Other examples of hydrotalcite utilization in esterification can be found in cited literature [134][135] . Aldol condensation is another example of important organic reactions for biomass upgrading, in particular, to fuels [136] .…”
Section: Biomass Upgradingmentioning
confidence: 99%
“…Kim et al [14] used a series of gold catalysts supported by hydroxyapatite and achieved an 89.3% yield of FDMC from HMF oxidative esterification in the absence of additional alkali. Recently, Li et al [15] found that the nano-gold catalyst supported by Mg-Al hydrotalcite showed good activity for DFF oxidative esterification, with a 96% yield of FDMC.…”
Section: Introductionmentioning
confidence: 99%